The Development OQEAC-Based Academic Supervision Management Model: Enhancing Quality and Performance - Junaina; Safitri Agustina; Tarekah Hasanah; Nirva Diana; Agus Pahrudin (Postgraduate Program Magister Pendidikan Agama Islam, 2025)
This study aimed to develop a scientifically-grounded academic supervision model using the OQEAC (Observing, Questioning, Experimenting, Associating, Communicating) framework to enhance the quality of teaching and professional development in Madrasah Ibtidaiyah in Tulang Bawang, Indonesia. The model was designed to address gaps identified in the existing academic supervision system, including inadequate teacher planning, ineffective learning processes, and the lack of authentic assessment practices. A systematic, evidence-based approach was employed to ensure that the model was tailored to meet the specific needs of teachers. After an in-depth literature review, needs analysis, and expert validation, a pilot trial was conducted with teachers and supervisors, yielding positive feedback on the model's practicality and effectiveness. The study's findings contribute to the growing body of research on improving academic supervision in Indonesia, offering an innovative, structured, and contextually relevant model for enhancing teacher competency and promoting continuous professional development. Future research is suggested to expand this model’s application to other educational contexts, particularly in urban and rural schools across Indonesia.